RETROFIT ALAT PENYULINGAN AKAR WANGI TRADISIONAL MENGGUNAKAN BOILER BERBAHAN BAKAR LIMBAH RAMAH LINGKUNGAN - anam, ahsonul (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2004)
Traditional distillation of akar wangi (Vetiveria zizanioides) using kerosene as a fuel has been used in small industries. The solid waste is burned in open air will emit strong odor which harmful to the environment. In fact, the waste has a caloric value of 3.800 kkal/kg, and by the proper handling, the waste can substitute part of the distillation process energy potentially and can reduce the environment impact caused by incomplete combustion or by the ingredient it self i.e. sulphur oxide and nitrogen oxide. To treat those waste, it is necessary to separate between distillation vessel with the steam generation system.